2022
DOI: 10.30762/jeels.v5i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Peer and Self Editing Strategies to Improve Students’ Writing Skill

Abstract: Peer and self editing strategies are social and metacognitive strategies used in the steps of sharing, revising, and editing in writing. The objective of the study is to see how peer and self editing strategies are able to improve students’ writing skill. 64 students participants were actively involved in this classroom action research. Peer editing worksheet, self editing worksheet, and test sheet were used as the instruments. The results showed that students’ writing skill improved in all elements: the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies explored the impact of peer and self-editing on writing. Abadikhah and Yasami (2014), Prabasiwi and Warsono (2017), and Winarto (2018) examined the effect of peer and self-editing strategies on learners' writing skills. All the aforementioned studies confirmed a positive impact of both the editing strategies on linguistic accuracy as well as writing performance.…”
Section: Peer Editing and Self-editingmentioning
confidence: 99%
“…Several studies explored the impact of peer and self-editing on writing. Abadikhah and Yasami (2014), Prabasiwi and Warsono (2017), and Winarto (2018) examined the effect of peer and self-editing strategies on learners' writing skills. All the aforementioned studies confirmed a positive impact of both the editing strategies on linguistic accuracy as well as writing performance.…”
Section: Peer Editing and Self-editingmentioning
confidence: 99%